Weight-centric prevention of cancer - Anazco, Diego; Acosta, Andres; Cathcart-Rake, Elizabeth J.; D'Andre, Stacy D.; Hurtado, Maria D. (Obesity Pillars (Online), 2024)
The link between excess adiposity and carcinogenesis has been well established for multiple malignancies, and cancer is one of the main contributors to obesity-related mortality. The potential role of different weight-loss interventions on cancer risk modification has been assessed, however, its clinical implications remain to be determined. In this clinical review, we present the data assessing the effect of weight loss interventions on cancer risk. In this clinical review, we conducted a comprehensive search of relevant literature using MEDLINE, Embase, Web of Science, and Google Scholar databases for relevant studies from inception to January 20, 2024. In this clinical review, we present systematic reviews and meta-analysis, randomized clinical trials, and prospective and retrospective observational studies that address the effect of different treatment modalities for obesity in cancer risk. In addition, we incorporate the opinions from experts in the field of obesity medicine and oncology regarding the potential of weight loss as a preventative intervention for cancer. Intentional weight loss achieved through different modalities has been associated with a reduced cancer incidence. To date, the effect of weight loss on the postmenopausal women population has been more widely studied, with multiple reports indicating a protective effect of weight loss on hormone-dependent malignancies. The effect of bariatric interventions as a protective intervention for cancer has been studied extensively, showing a significant reduction in cancer incidence and mortality, however, data for the effect of bariatric surgery on certain specific types of cancer is conflicting or limited. Medical nutrition therapy, exercise, antiobesity medication, and bariatric interventions, might lead to a reduction in cancer risk through weight loss-dependent and independent factors. Further evidence is needed to better determine which population might benefit the most, and the amount of weight loss required to provide a clinically significant preventative effect.